Branched amphiphilic peptides: an alternate non-viral gene delivery system - Avila Flores, Luz Adriana (Kansas State University, 2014)
Success for gene therapy clinical protocols depends on the design of safe and efficient gene carriers. Nature had already designed efficient DNA or RNA delivery devices, namely virus particles. However, the risk of insertional mutagenesis has limited their clinical use. Alternatively, safer approaches involving non-viral carriers have been and continue to be developed. While they have been reported to be less efficient than viral vectors, adding genome editing elements to pDNA makes the integration of corrective sequence site specific moving non-viral gene delivery systems closer to clinical applications. Over the last decade, peptides have emerged as a new family of potential carriers in gene therapy. Peptides are easy to synthesize, quite stable and expected to produce minimally immunogenic and inflammatory responses. We recently reported on a new class of Branched Amphiphilic Peptides Capsules (BAPCs) that self-assemble into extremely stable nano-spheres. BAPCs display a uniform size of _20 nm if they are incubated at 4_C and they retain their size at elevated temperatures. In the presence of DNA, they can act as cationic nucleation centers around which DNA winds generating peptide-DNA complexes with a size ranging from 50nm to 100nm. However, if BACPs are not incubated at 4_C, the pattern of interaction with DNA differs. Depending of the peptide/DNA ratios, the peptides either coat the plasmid surface forming nano-_bers (0.5-1 _M in length) or condense the plasmid into nano-sized structures (100-400nm). Different gene delivery efficiencies are observed for the three types of assemblies. The structure where the DNA wraps around BAPCs display much higher transfection efficiencies in HeLa cells in comparison to the other two morphologies and the commercial lipid reagent Lipofectinr. As a proof of concept, pDNA was delivered in vivo, as a vaccine DNA encoding E7 oncoprotein of HPV-16. It elicited an immune response activating CD8+ T cells and provided anti-tumor protection in a murine model.
Keywords: Celullar biology; Molecular biology; Biochemistry; Chemistry; Biophysics; Biogeochemistry (0425); Biophysics (0786); Cellular Biology (0379)